Récits du corps au Japon - Marc Kober (Itinéraires)
The body matter can be transferred to Japan history as “sakoku” (鎖国), a very long isolated country. Japanese body would build up through symbolic stories and views describing natives’ nature and culture in contrast with foreigner’s body. Is the body omnipresence in Japanese stories significant for all that? The narrative construction of the Japanese body goes through a genealogy, a whole inherited native cultural mediations before the great confrontation with the West. The literature would confirm not so the existence of a body image as a relation to others opening up a specific body field. The story of an improbable “Japanese body”, tale for inner and outer use, and as such is a party to a western contemporary view.